Practice Variation in the Management of First Trimester Miscarriage in The Netherlands: A Nationwide Survey - Marianne A. C. Verschoor; Marike Lemmers; Malu Z. Wekker; Judith A. F. Huirne; Mariëtte Goddijn; Ben Willem J. Mol; Willem M. Ankum (Obstetrics and Gynecology International)
Objectives. To survey practice variation in the management of first trimester miscarriage in The Netherlands. Methods. We sent an online questionnaire to gynecologists in eight academic, 37 nonacademic teaching, and 47 nonteaching hospitals. Main outcome measures were availability of a local protocol; estimated number of patients treated with curettage, misoprostol, or expectant management; misoprostol regimen; and estimated number of curettages performed after initial misoprostol treatment. Outcomes were compared to the results of a previous nationwide survey. Results. The response rate was 100%. A miscarriage protocol was present in all academic hospitals, 68% of nonacademic teaching hospitals, and 38% of nonteaching hospitals (P=0.008). Misoprostol was first-choice treatment for 41% of patients in academic hospitals versus 34% and 27% in teaching-and nonteaching hospitals (P=0.045). There were 23 different misoprostol regimens. Curettage was first-choice treatment in 29% of patients in academic hospitals versus 46% and 50% in nonacademic teaching or nonteaching hospitals (P=0.007). In 30% of patients, initial misoprostol treatment was followed by curettage. Conclusions. Although the percentage of gynaecologists who are aware of the availability of misoprostol for miscarriage treatment has doubled to almost 100% since 2005, practice variation is still large. This practice variation underlines the need for a national guideline.